Melatonin Improves Liver and Pancreatic Tissue Injuries in Diabetic Rats: Role on Antioxidant Enzymes - Ertik, Onur; Bayrak, Bertan Boran; Sener, Goksel; Yanardag, Refiye (Springer int Publ Ag, 2023)
PurposeMelatonin (Mel) is an indolamine mainly synthesized by the pineal gland and many other organs. It plays an important role in scavenging free radicals and stimulating antioxidant enzymes. The goal of this study was to investigate the effect of Mel and/or insulin treatment on oxidative liver and pancreas injuries in diabetic rats.MethodsMale Wistar albino rats were assigned into 5 groups. Group I: control animals. Group II: diabetes was induced via a single dose of STZ (60 mg/kg) administered intraperitoneally. Group III: diabetic rats treated with Mel (10 mg/kg/day). Group IV: diabetic rats given insulin (6U/kg) subcutaneously. Group V: diabetic rats that received insulin and Mel at the same dose and time. After 12 weeks of the experiment, the animals were decapitated, liver and pancreas tissues were collected.ResultsThe results indicated that reduced glutathione levels in liver and pancreatic tissue decreased, while protein carbonyl, advanced oxidized protein products and lipid peroxidation levels were elevated in diabetic group. Antioxidant enzyme activities decreased in liver tissues but increased in pancreatic tissues of the diabetic group. Administration of Mel, insulin or Mel + insulin reversed these biochemical changes in the diabetic animals.ConclusionThis work shows that in long-term oxidative stress conditions caused by STZ-induced diabetes, either Mel or Mel + insulin administration may improve the deteriorated oxidant/antioxidant system in both the liver and pancreas tissues. These results suggested that Mel alone or Mel + insulin treatments might have a significant role in protecting against liver and pancreatic damage in STZ diabetic rats via different antioxidant effects.
ERTIK, Onur/0000-0001-5437-3513; BAYRAK, Bertan Boran/0000-0002-0700-5096; Sener, Goksel/0000-0001-7444-6193
Keywords: Diabetes; Liver; Pancreas; Insulin; Melatonin; Antioxidant Enzymes